24-6x=-6(x-4)

Simple and best practice solution for 24-6x=-6(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24-6x=-6(x-4) equation:



24-6x=-6(x-4)
We move all terms to the left:
24-6x-(-6(x-4))=0
We calculate terms in parentheses: -(-6(x-4)), so:
-6(x-4)
We multiply parentheses
-6x+24
Back to the equation:
-(-6x+24)
We get rid of parentheses
-6x+6x-24+24=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 0.08(y-2)+0.16y=0.04y-1.5 | | 5x+11=12x-59 | | 7x−7=3x−23 | | 3=x+28 | | -x+8x=64 | | 7x-7=3x−23 | | x+.21x=651.67 | | 15=2u-5 | | 5=x+52 | | -3+2=2x+37 | | 8x3=(−2x)(A) | | -3u-10=17 | | 4^2x–5=64 | | 2(2x-1)=2(4x+7) | | 35=3v+8 | | q+16=6 | | 81/3=6y+3y | | q+15=6 | | 136=(10x-8) | | 2x/6=96 | | –3.7x=29.6 | | q-19=17 | | (13x-16)=(9x+4) | | 5x-6-1x=2x+2 | | n+75=175 | | 24=(w+2) | | -10x+5=-8x+11 | | 3z-(z/2+5)=10 | | h+13=33 | | 4r+32/12=4r-24/4 | | 3y-13=-13 | | x/4=2.5^2 |

Equations solver categories